2021
DOI: 10.1111/ijfs.15507
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals and bioactivities of Goji (Lycium barbarum L. and Lycium chinense Mill.) leaves and their potential applications in the food industry: a review

Abstract: Goji leaves, including Lycium barbarum L. and Lycium chinense Mill. leaves, have been used as traditional Chinese medicine materials for nourishing kidneys and enhancing eyesight but are mostly discarded at present. The nutritional composition of Goji leaves is similar to that of Goji berries even some components are more plentiful in the former, such as flavonoids. This paper firstly reviews the main phytochemicals of Goji leaves. Also, updated information on the biological activities of Goji leaves is narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Furthermore, the species variability of sacsaoul and goji berry is also an important factor contributing to the difference in their photosynthetic sequestration capacity. Goji berry is a multi-stemmed shrub with single alternate or clustered leaves, mostly ovate, ovate-rhombic, and ovate-lanceolate, with a small photosynthetically effective area (Lei et al, 2021). Sacsaoul is a small tree with scale-like, broadly triangular leaves, and a large photosynthetically effective area (Gao et al, 2010).…”
Section: Effects Of Land Use Change On Soil Carbon and Gwpmentioning
confidence: 99%
“…Furthermore, the species variability of sacsaoul and goji berry is also an important factor contributing to the difference in their photosynthetic sequestration capacity. Goji berry is a multi-stemmed shrub with single alternate or clustered leaves, mostly ovate, ovate-rhombic, and ovate-lanceolate, with a small photosynthetically effective area (Lei et al, 2021). Sacsaoul is a small tree with scale-like, broadly triangular leaves, and a large photosynthetically effective area (Gao et al, 2010).…”
Section: Effects Of Land Use Change On Soil Carbon and Gwpmentioning
confidence: 99%
“…Pharmacological studies have shown that polysaccharides, total phenols, total flavonoids, and other functional compounds in drying-processed wolfberries are immune-supportive, anti-tumorigenic, and have anti-aging effects [ 4 , 5 ]. The moisture content of ripe, fresh wolfberry fruit can reach more than 80%, and the fruit has a high sugar content and is sensitive to microbial deterioration, causing it to rot easily during harvest and storage [ 6 ]. Therefore, harvested fresh wolfberry must be dehydrated to a safe moisture content in a timely manner to facilitate subsequent transportation, storage, and processing.…”
Section: Introductionmentioning
confidence: 99%
“…The leaves of Lycium barbarum L. are abundant in active substances. For instance, flavonoids, phenolic acid, terpenoids, alkaloids, sterols and polysaccharides (Masci et al., 2018; Lei et al., 2022; Wang et al., 2022). And Lycium barbarum L. leaves flavonoids (LBLF) are the main phenolic compounds in nature (Li et al., 2022), with antioxidant, anti‐ageing, fat reduction and other effects (Chen et al., 2020; Liao et al., 2022; Niu et al., 2022).…”
Section: Introductionmentioning
confidence: 99%